Catechol‐O‐Methyltransferase Genotype and Gait Speed Changes over 10 Years in Older Adults. Issue 9 (22nd June 2017) - Metti, Andrea L.; Rosano, Caterina; Boudreau, Robert; Massa, Robyn; Yaffe, Kristine; Satterfield, Suzanne; Harris, Tamara; Rosso, Andrea L.
Abstract : Objectives: To determine the association between catechol‐O‐methyltransferase (COMT) genotype and 6‐m walk time and to determine whether these associations are quadratic in nature, similar to previously reported U‐shaped associations between dopamine and gait and cognition. Design: Prospective cohort study. Setting: Health, Aging and Body Composition Study. Participants: Black (n = 850) and white (n = 1, 352) men and women with a mean age of 73.5 ± 2.85 at baseline. Measurements: Mixed models were used to assess the association between the COMT genotype and 6‐m walk time, cross‐sectionally and longitudinally over 10 years. Models were assessed unstratified and stratified according to race because allele distributions were different between white and black participants. Results: There was a significant U‐shaped association between COMT genotype and 6‐m walk time: those with higher (Val/Val) and lower (Met/Met) dopamine slowed more over 10 years (0.22 ± 0.02 seconds per visit and 0.23 ± 0.02 seconds per visit, respectively) than those with the intermediate (Met/Val) dopamine (0.20 ± 0.02 seconds per visit) ( P = .005). Stratified results showed a significant relationship in black ( P = .01) but not white ( P = .15) participants. Conclusion: These findings indicate a role of dopaminergic regulation of gait speed in community‐dwelling older adults and of prefrontal cortex involvement in gait performance. Future work should investigate the molecular integrity of dopaminergic networks and gait changes over time and structural changes in the brain with COMT and gait decline in older adults.